Role of Wireless Sensor Network in Precision Agriculture - Haifa Alqahtani (Computational Algorithms and Numerical Dimensions)
In Agricultural Fields there are different climate conditions, greenhouses parameters are important to monitored regulate the crop production, and we would like to make a automation system to trace down climate conditions at different locations. The Wireless Sensor Network (WSN) do the job to automate and analyze the comparable parameters. We would like to develop a smartphone application and sensors used are electrochemical sensors, location sensors BeagleBone Controller and Various Sensors are Used.